Understanding the relationship between construction costs and selling prices with specific reference to housing projects in the Klang Valley - Abdul Rashid, Khairuddin; Hasan, Sharina Farihah (International Business Information Management Association, IBIMA, 2015)
Debates on the continuous and upward increase in the selling price of houses continue unabated. However, very little has been said about construction costs of houses, such as, is the trend in construction costs of houses moving in similar patterns too? One way to understand it is through comparing and contrasting the construction costs index against the selling price index of housing projects. This paper reports on a study into historic cost and price movements of newly built housing in the Klang Valley. The study endeavors to seek answers to the following key questions: (i) is the construction costs of houses moves in similar pattern with the movement of house prices; and (ii) is construction costs of houses moves in similar pattern with the movement in the economy? The methodology for the study starts with the identification of appropriate indices for both construction costs and selling prices of houses in the Klang Valley. While there is house price index published by NAPIC but there is no published data on construction costs price index of houses. In addition, the NAPIC house price index does not differentiate between the selling prices of new or second-hand houses. Consequently, the study constructed its own construction costs and house price indices for new houses. Data on construction costs of houses (all types), was acquired via a questionnaire survey among quantity surveyors and contractors. In the case of selling prices of houses, data was acquired from newspaper archives and websites with records on advertisements for new houses. The period covered in the study is for the duration from 2005 to 2013. The constructed indices were validated via discussions with experts representing the Malaysian housing sector and academics. The outcome of the study, in terms of the relationship between construction costs and selling prices of houses, the indices suggested that construction costs moves upwards along similar pattern with that of the selling prices but the upward movement in costs is relatively much higher than that of prices. In addition, in terms of the relationship between construction costs of houses and the economy (GDP) the indices suggested that construction costs moves upwards along similar pattern with that of the economy but the upward movement in costs is relatively higher than that of the economy. Furthermore, the indices suggested that selling prices of houses moves in tandem with the economy. The paper concludes that there is positive relationship in terms of upward movements between construction costs, selling prices and the economy during periods of economic growth.